Chapter Boccaccio erudito e il prologo del De viris illustribus petrarchesco - Ceccarelli, Chiara (Studi e saggi, 2020)
Giovanni Boccaccio used prologues and epilogues of his Latin works to discuss relevant topics such as the finding of reliable sources or the dissamination of the knowledge. Francesco Petrarca faced the same issues when he wrote his scholarly and historical works. This paper aims at enlightening the intertextuality between prologues and epilogues of Boccaccio's Genealogia and De montibus and the prologue of Petrarca's De viris illustribus, showing that the formers were probably inspired by the latter.